Factors Predicting Early Failure of Etanercept in Rheumatoid Arthritis: An Analysis From the Gruppo Italiano di Studio sulla Early Arthritis (Italian Group for the Study of Early Arthritis) Registry - Rosario FOTI; Giovanni LAPADULA; Gianfranco FERRACCIOLI; Luca PETRICCA; Giuseppe LOPALCO; Giulia CASSONE; Alberto CAULI; Roberto CAPORALI; Chiara GIANNITTI; Marco SEBASTIANI; et al. (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the factors associated with early discontinuation (within one year) of etanercept (ETA) in rheumatoid arthritis (RA) patients who began ETA as first biologic disease-modifying antirheumatic drug (bDMARD) and who were entered into the Gruppo Italiano di Studio sulla Early Arthritis (Italian Group for the Study of Early Arthritis; GISEA) registry. Patients and methods: This registry-based cohort study included 477 RA patients (95 males, 382 females; median age 53 years; range 18 to 83 years) who began ETA as first bDMARD. Patient demographics, disease features and drugs were re-evaluated after 12 months. Baseline predictors of ETA discontinuation were estimated by univariate and multivariate analyses using Cox regression model. Results: Seventy patients (14.7%) discontinued ETA during the first year (for inefficacy in 55.8%, adverse events in 28.6%, and other reasons in 6.5%). Concurrent conventional synthetic DMARDs (csDMARDs) were reported in 54.3% of patients, mainly methotrexate (MTX), while 52.4% of subjects took low doses of glucocorticoids. Patients stopping ETA more frequently showed one or more comorbidities, mainly cardiovascular diseases (28.6% vs. 15.7% in patients stopping and continuing ETA, respectively, p=0.009). The presence of comorbidities and a combination therapy with csDMARDs other than MTX were independent factors associated with early discontinuation of ETA at multivariate Cox analysis. Conclusion: Although ETA demonstrated a high persistence in biologic-naïve RA patients, about 15% of patients discontinued the treatment within 12 months. The presence of comorbidities and a combination therapy with csDMARDs other than MTX were the main factors for an early withdrawal of the drug.